ANALISIS PERSEDIAAN BAHAN BAKU DAN STRATEGI PENGEMBANGAN AGROINDUSTRI KERIPIK SINGKONG DI KABUPATEN BONDOWOSO - Rofika Fitrah; Imam Syafi'i; Titin Agustina (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
This study aims to determine:(1) the level of inventories of cassava as raw materials to minimize the cost of inventory on cassava chips agro-industry in Bondowoso, (2) the level of re-ordering (reorder point) cassava chips and cassava in the agro-industry in Bondowoso, and (3) development strategy of cassava chips agro-industry in the Bondowoso regency. Area the study determined intentionally (purposive method) in the Bondowoso regency. The type of data used primary data and secondary data. Methods of data analysis using EOQ analysis, ROP, and SWOT. The results showed that: (1) the level of inventories cassava as raw materials in cassava chips agro-industry domestic scale and small scale uneconomical. EOQ on agro-scale cassava chips households amounted to 181.2 kg. EOQ on agro-industry small-scale cassava chips amounted to 279.4 kg, (2) Level of reordering cassava or Reorder Point (ROP) agro-industry domestic scale cassava chips is by 64 kg and the booking rate back raw materials or Reorder Point (ROP) on agro-industry small-scale cassava chips is equal to 320 kg. Scale agro-industries and small-scale household has a level reordering (ROP) is equal to the amount of the initial booking, each of which is 64 kg and 320 kg so it is said to have shortage of cassava as raw material, (3) agro-industry development strategy for cassava chips in the regency (strategy SO) as follows: (a) Cassava chips agro-industry domestic scale: Increase productivity and maintain existing markets, (b) Cassava chips agro-industry small scale: Maintaining existing markets, expand market reach and increase productivity.